(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The effect of light-induced rotation of the laser radiation polarization ellipse in a non-gyrotron solution of aminoacetic acid was experimentally investigated. The dependences of the rotation angle on the energy and polarization characteristics of the laser radiation, as well as the degree of protonation of the solution, were studied. The physicochemical causes of this effect are discussed.